1992
DOI: 10.1007/bf00353906
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical and circadian biochemical analysis of neuroactive amino acids in the pineal gland of the rat: effect of superior cervical ganglionectomy

Abstract: Semiquantitative immunocytochemistry by immuno-gold techniques revealed differences in the spatial distribution of glutamate, glutamine, and taurine within the pineal gland, with greatest labeling over pinealocytes, glia, and endothelia, respectively. At the subcellular level, glutamate labeling tended to be highest over pinealocyte synaptic ribbons and mitochondria, and lowest over lipid inclusions. Pineal levels of glutamate, glutamine and taurine, as measured by high performance liquid chromatography, did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…display additional autocrine/paracrine effects. Pineal cells also contain GABA (15% of bovine pineal cells: Rosenstein et al, 1989b), Glu (McNulty et al, 1992), aspartate (Imai et al, 1995), and taurine (LaBella et al, 1968), which are able to alter the metabolic activity of the pineal gland (see Section VI.B.). Intrapineal neurons immunopositive for acetylcholinesterase have been identified in the pineal gland of several mammalian species (Romijn, 1975;.…”
Section: Paracrine Inputsmentioning
confidence: 99%
“…display additional autocrine/paracrine effects. Pineal cells also contain GABA (15% of bovine pineal cells: Rosenstein et al, 1989b), Glu (McNulty et al, 1992), aspartate (Imai et al, 1995), and taurine (LaBella et al, 1968), which are able to alter the metabolic activity of the pineal gland (see Section VI.B.). Intrapineal neurons immunopositive for acetylcholinesterase have been identified in the pineal gland of several mammalian species (Romijn, 1975;.…”
Section: Paracrine Inputsmentioning
confidence: 99%
“…Pinealocytes are known to contain relatively high concentration of glutamate [9] and a large number of synaptic-like microvesicles (MVs) [10]. Recent evidence indicated that MVs *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…This strong immunoreactivity has previously been demonstrated in the so-called dark pinealocytes of the pigeon (UECK et al, 1995). In contrast, a uniform distribution of taurine within pinealocytes, glia, and sympathetic fibers has been reported in the pineal gland of the rat (MCNULTY et al, 1992).…”
Section: Discussionmentioning
confidence: 80%
“…High levels of taurine immunostaining were found in the outer and inner segments and synaptic terminals of some photoreceptor cells; lower levels of immunostaining were reported in the apical processes of pigment epithelium and distal parts of glial cells (LAKE and VERDONE-SMITH, 1989;Pow, 1994). The taurine localization, however, is scarcely known in the photoneuroendocrine pineal organ, except in the case of the pigeon (DECK et al, 1995) and rat (MCNULTY et al, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation